The Effect of Home Visits by Midwives on Increasing Compliance with High-Risk Pregnancy Examinations at the Rumbalibunga Tidore Health Center - Huwiani Huwiani; Rani Safitri (Calory Journal Medical Laboratory Journal, 2025)
Several things contribute to the rise in Indonesia's Maternal Mortality Rate (AKI), one of which is how moms behave and think while they are pregnant. If pregnant women don't follow the recommended schedule for antenatal care (ANC) exams, a number of pregnancy issues may go unnoticed at an early stage, which may have an impact on the pregnancy process, childbirth, the postpartum period, and the health of the child being born. As a result, midwife visits play a key role in improving pregnant women's adherence to ANC tests via education, mentorship, and close supervision. The goal of this study is to assess the impact of midwife appointments on pregnant women's adherence to ANC exams at the Rumbalibunga Tidore Health Center UPT. With a cross-sectional research design, this study employs a quantitative methodology. This research focuses on 66 pregnant women who are enrolled in the Rumbalibungan Health Center UPT's working area in Tidore. Total sampling, which utilizes the entire population as a research sample, is the method employed. The chi-square test was used in bivariate analysis to investigate the impact of midwife visits on antenatal care (ANC) examination compliance, while univariate analysis was performed to describe the frequency and percentage distribution of each variable. The majority of participants, or 51.5%, had not followed the recommended antenatal care (ANC) exams, according to the data. After a midwife's visit to the home, which served as an intervention, there was an increase in the compliance of pregnant women in having ANC tests. The chi-square test yielded a p-value of 0.021 (p < 0.05) in the statistical analysis, indicating that the midwife's home visit has a substantial impact on adherence to the ANC examination. According to the study's findings, the UPT Puskesmas may enhance its coaching operations to the community by providing frequent home visits and health education, particularly to expectant mothers and women of reproductive age. The instruction covers pregnancy preparation, the value of antenatal care (ANC) exams, the optimum time to begin pregnancy exams, and the timeline for follow-up exams. Consequently, it is hoped that pregnant women will adhere to the service standards established for pregnancy tests, which call for at least four tests throughout the course of the pregnancy.